2023
DOI: 10.20854/bujse.1210891
|View full text |Cite
|
Sign up to set email alerts
|

Hub and Distribution Center Location for a Third-Party Logistics service Provider: A Case Study at Tehran

Abstract: The rapid growth of the transportation industry and the advance of the e-commerce have opened opportunities for boom delivery services companies. Although, intense competition between shipping companies has obliged many to amend their shipment networks. In this setting, we aim to provide high-quality shipping services for a third-party logistics company in Iran. Currently, in the selected company, one hub is in the west part of Tehran that gives services to all customers. There are some difficulties in shippin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Based on previous research, researchers identified 15 dimensions/factors that influence the logistics system in island countries. Those dimensions/factors include demand (Zakharchuk et al, 2022), availability of raw materials (Desai & Bohara, 2021), quality of handling (Okyere et al, 2018;Elis Dwiana Ratnamurni et al, 2022), quality of documentation and logistics information (Muslimov & Shaburova, 2021), reliability of delivery time (Ehmke & Mattfeld, 2010), timing accuracy (Pendem, 2019;Chondrodima et al, 2022;Ogura et al, 2021), costs (Hasanpour Jesri et al, 2023;Cheng et al, 2022;Zakharchuk et al, 2022;Okyere, 2018), warehousing (Sivakumar, 2019), logistics infrastructure capacity (Wang, 2021), connectivity (Bevilacqua, 2022;Pistilli, 2020), services (Anas et al, 2020;Sadowska et al, 2020;Bazaras et al, 2023), institutional (Yashin et al, 2023), competence (Dwijaya Saputra & Kusnadi, 2021Zamkova et al, 2023), education and training (Liu & Yang, 2023), automation (Singh, 2018;Song, 2021).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Based on previous research, researchers identified 15 dimensions/factors that influence the logistics system in island countries. Those dimensions/factors include demand (Zakharchuk et al, 2022), availability of raw materials (Desai & Bohara, 2021), quality of handling (Okyere et al, 2018;Elis Dwiana Ratnamurni et al, 2022), quality of documentation and logistics information (Muslimov & Shaburova, 2021), reliability of delivery time (Ehmke & Mattfeld, 2010), timing accuracy (Pendem, 2019;Chondrodima et al, 2022;Ogura et al, 2021), costs (Hasanpour Jesri et al, 2023;Cheng et al, 2022;Zakharchuk et al, 2022;Okyere, 2018), warehousing (Sivakumar, 2019), logistics infrastructure capacity (Wang, 2021), connectivity (Bevilacqua, 2022;Pistilli, 2020), services (Anas et al, 2020;Sadowska et al, 2020;Bazaras et al, 2023), institutional (Yashin et al, 2023), competence (Dwijaya Saputra & Kusnadi, 2021Zamkova et al, 2023), education and training (Liu & Yang, 2023), automation (Singh, 2018;Song, 2021).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%